STRATEGI PENGELOLAAN PROGRAM HUTAN KEMASYARAKATAN (HKm) DI KESATUAN PENGELOLAAN HUTAN PRODUKSI BARITO TENGAH - Mulkarim, Muhammad Halim; Hafizianoor, Hafizianoor; Kadir, Syarifuddin (Lambung Mangkurat University-Indonesia, 2024)
The aim of this research is to formulate a strategy for community forest management in the Central Barito Production Forest Management Unit. Data analysis used the SWOT formula with planning techniques to evaluate strengths, weaknesses, opportunities and threats in a project. The research object is the Datah Berbuahl Forest Farmer Group in Sei Rahayu II Village with SK KTH SK.2580/MENLHK-PSKL/PKPS/PSL.0/4/2018 and the Karya Bersama Forest Farmer Group in Hajak Village with SK KTH SK.7132/MENLHK-PSKL/PKPS/PSL.0/4/2019. The selection of informants for interviews in the Focus Group Discussion was carried out deliberately to represent groups of community forest farmers who have influence in making group decisions and representatives of informants related institutions in community forestry programs, such as the KPHP Central Barito, NGOs/Customary Heads and Village Heads. The results of the SWOT matrix are built based on the results of an analysis of external and internal strategic factors, there are four main strategies, namely utilizing the availability of large enough land (SO), improving road access to the location of Forest Farmers Groups (WO), designating clear forest areas (ST) and increasing farmers' interest in managing Hkm (WT). The score calculation results on the matrix based on the EMP development strategy in North Barito Regency are in quadrant I (0.62; 0.29). Quadrant I (Strategy Aggressive), that is, with the strengths possessed by forest farmer groups, they must be able to take advantage of existing opportunities, while overcoming all weaknesses that arise and constitute a profitable situation, forest farmer groups have opportunities and strengths so that they can take advantage of existing opportunities.